Analysis of Full Day School Policy on Islamic Religious Education Learning at SDIT Plus Usman Bin Ali Medan - Raisya Afifah Zahra; Elva Savira; Muhammad Dandi Nugroho; Ranisa Ramadhani; Sahrul; Mifta Mairani Noor (Jurnal Pendidikan Islam, 2025)
This study aims to examine the full day school policy in Islamic Religious Education learning at SDIT Plus Usman Bin Ali Medan. This research employs a qualitative method with a descriptive study design. Data were collected through in-depth interviews and observations regarding the full day school policy in Islamic Religious Education learning at SDIT Plus Usman Bin Ali Medan. The data were analyzed using the Miles and Huberman model and validated through triangulation. The results show that the full day school policy in Islamic Religious Education learning at SDIT Plus Usman Bin Ali Medan has proven to be an effective solution in shaping a rabbani generation that is intelligent and possesses noble character, in line with the school’s vision and mission. It is expected that this research can serve as an additional reference and provide insight for other SDIT Plus schools or, more broadly, regarding the implementation of the full day school policy in Islamic Religious Education.